Bioconversion of municipal organic solid waste in to compost using Black Soldier Fly (Hermetia Illucens) - Priscilla Addo; Sampson Oduro-Kwarteng; Samuel Gyasi; Esi Awuah (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The study assessed the quality of compost produced by the Black Soldier Fly Larvae (BSFL) in terms of the compost nutrient level, microbial activities, and the bioaccumulation of possible heavy metals in the organic solid waste.Method The study used the pre-experimental study design, one-group pretest-posttest to obtain the data. Five experimental units were used for the study, which include the daily feeding rate for the five different groups of larvae. The experiments were replicated three times. The nutrient level, heavy metal content and presence of microbes were analyzed before and after the decomposition process.Results The study discovered that the Nitrogen, Phosphorus and Potassium (NPK)content   increased in the compost produced. Cross-contamination of Total Coliform from feed to the prepupae were significant while regrowth of Total Coliform in compost were insignificant. After the composting process most heavy metals like Fe had insignificantly increased in the compost .Conclusion It can be concluded that larval composting enhance the regrowth of pathogens since the process is entirely mesophilic. Bioaccumulation of most heavy metals was minimum, increasing the level of these heavy metals in the compost. The nutrients were extremely high in the compost to the extent that can cause phyto-toxicity. Post-treatment of the compost is needed to make BSFL compost viable for the market.